Processed data from SeaExplorer SEA070 in the Amundsen Sea, 2022, as part of the TARSAN and ARTEMIS deployments on cruise NBP2202. - Śliwiński, Jan Jakub; Oliver, Hilde; Queste, Bastien (University of Gothenburg, 2026)
This dataset contains processed Level-3 glider observations from SeaExplorer SEA070 (“Scratch”) collected in the Amundsen Sea during the NBP2202 expedition in early 2022. It forms part of the TARSAN and ARTEMIS efforts associated with the International Thwaites Glacier Collaboration. TARSAN focused on how atmosphere–ice–ocean interactions influence the Thwaites and Dotson ice shelves, using gliders, ship surveys, AUVs, moorings, and CTDs to characterize ocean conditions on the continental shelf and beneath ice shelves. ARTEMIS complemented that work by adding biogeochemical observations, especially from autonomous platforms, to investigate how West Antarctic Ice Sheet melt affects ecosystem structure and regional carbon cycling.

In the processed file, SEA070 is represented as a trajectory/timeseries-style product gridded to 1100 depth levels and 492 profiles, spanning about mid-January to mid-February 2022 in the eastern Amundsen Sea near 72.2–72.4°S, 117.9–117.3°W. The dataset includes core hydrography from an RBR Legato CTD (temperature, conductivity, salinity, pressure), dissolved oxygen from an RBR Coda sensor, nitrate from a Sea-Bird Deep SUNA, and optical measurements from a WET Labs ECO Puck FLBBCD (chlorophyll, CDOM, backscatter), together with derived products such as density, potential temperature, mixed-layer depth, euphotic depth, light fields, corrected chlorophyll, corrected nitrate, and corrected oxygen.

Note that there was a severe CTD electrical noise issue affecting conductivity, absolute values are OK but the data is incredibly noisy. The oxygen calibration is also imperfect; and absolute values should be treated with caution.
Keywords: Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser